Does parkinsonian action tremor contribute to muscle weakness in Parkinson's disease? - Brown, P; Corcos, D; Rothwell, J (1997)
The aim of this study was to see whether action tremor contributes to the weakness which can be measured in some muscles in patients with Parkinson's disease, by preventing fully fused contraction of motor units. Strength and action tremor were recorded during maximal wrist extension in patients when they were on and off antiparkinsonian medication, and in age- and sex-matched healthy subjects. Peak torque and mean rectified EMG levels were reduced by 25% and 30% (n = 7), respectively, when patients were off medication (compared with when they were on medication). In parkinsonian patients off treatment, action tremor was visible in torque and EMG records, and had a frequency of approximately 10 Hz. The absolute amplitude of this tremor was considerably smaller in patients on medication and in control subjects. In patients, medication reduced action tremor in torque and EMG by 37% and 57%, respectively, so that tremor amplitude approached that in normals. Similar changes were seen when action tremor was expressed as % peak torque of % mean rectified EMG. In parkinsonian patients off medication, a 10-Hz synchronizing influence dominates muscle activity at the wrist. The results is an incompletely fused muscle contraction, which is an important factor contributing to the weakness present in the off-medication state. Antiparkinsonian medication releases motor units from the 10-Hz synchronizing influence, enabling higher discharge rates, fused contraction and improved force generation.